Oor die kerk en maatskaplike uitdagings in ons land - Smit, DJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
On the church and social challenges in our country The way people see the role of the church regarding public and social challenges, including poverty, inevitably depends on which form (“gestalte”) of the church they regard as primary. The church as congregation is called to worship and pray – with important implications for social needs and problems, including the formation and motivation of moral agents. These worshipping believers are called to join hands as members of congregations – making new kinds of joint activities and initiatives possible. Congregations are called to join one another in the koinonia of the fellowship of the church – including, within Protestantism, denominations, which makes even more comprehensive forms of activity, response and service possible. Denominations are called to express the even fuller unity of the church ecumenically – allowing attempts to address the more widespread and fundamental roots of the social problems, as well as to play advocacy roles on behalf of the voiceless. In the last resort, the church consists of individual believers, the salt of the earth, who are called to follow Jesus – practising the Christian life in all aspects of public sphere, politically, economically, civil society, everywhere. These disciples are called to join hands with one another and also with others not sharing their faith – in order to work for specific purposes and tasks in society, for example, by initiating and supporting programmes and forming partnership and networks. Taken together, these six different emphases provide a fuller picture of what church really means and what the role and calling of the church, also in the face of poverty, could be.